Penerapan Pendekatan Montessori dalam Pembelajaran di Kelas Awal SD - Bakar, Abu (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2023)
This study aims to analyze the implementation of the Montessori approach in early-grade elementary school learning and its impact on students' basic skills. This research is a quantitative study with an experimental approach. The subjects of this study are early-grade elementary school students, while the object is the application of the Montessori approach in the learning process. Data collection techniques include observation, tests, and interviews. The collected data were analyzed using descriptive quantitative analysis, calculating the average score and comparing the learning outcomes before and after the implementation of the Montessori method. The results indicate that the application of the Montessori method enhances students' basic skills in reading, writing, and arithmetic. The implementation of this method also increases students' interest in learning and helps them overcome learning difficulties, such as math anxiety. In conclusion, the Montessori approach is effective in improving the quality of learning in early-grade elementary schools, providing a more enjoyable and developmentally appropriate learning experience for students..